Rapid identification of antibiotic resistance using droplet microfluidics. Issue 2 (2nd April 2016) - Keays, Marie C.; O'Brien, Mark; Hussain, Anam; Kiely, Patrick A.; Dalton, Tara
ABSTRACT: Culturing bacteria and monitoring bacterial cell growth is a critical issue when dealing with patients who present with bacterial infections. One of the main challenges that arises is the time taken to identify the particular strain of bacteria and consequently, decide the correct treatment. In the majority of cases, broad spectrum antibiotics are used to target infections when a narrow spectrum drug would be more appropriate. The efficient monitoring of bacterial growth and potential antibiotic resistance is necessary to identify the best treatment options for patients. Minturising the reactions into microfluidic droplets offers a novel method to rapidy analyze bacteria. Microfluidics facilitates low volume reactions that provide a unique system where each droplet reaction acts as an individual bioreactor. Here, we designed and built a novel platform that allowed us to create and monitor E.coli microfluidic droplet cultures. Optical capacity was built in and measurements of bacterial cultures were captured facilitating the continuous monitoring of individual reactions. The capacity of the instrument was demonstrated by the application of treatments to both bacteria and drug resistant strains of bacteria. We were able to detect responses within one hour in the droplet cultures, demonstrating the capacity of this workflow to the culture and rapid characterization of bacterial strains.